Enantiospecific Total Synthesis of N‐Methylwelwitindolinone D Isonitrile1. Issue 47 (2nd October 2013) - Styduhar, Evan D.; Huters, Alexander D.; Weires, Nicholas A.; Garg, Neil K.
<x xml:space="preserve">Abstract</x> The total synthesis of N‐methylwelwitindolinone D isonitrile (1) has been achieved in 17 steps from a readily available carvone derivative. The route features a double C–H functionalization event involving a keto oxindole substrate to introduce the tetrahydrofuran ring of the natural product.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>